2020
DOI: 10.1177/0964528420907338
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture stimulation attenuates TNF-α production via vagal modulation in the concanavalin A model of hepatitis

Abstract: Background: A growing body of evidence shows that neuronal activity is involved in modulating the efficacy of acupuncture therapy. However, it has been seldom investigated whether neuronal activity following acupuncture stimulation is effective at regulating hepatic inflammation. Objective: Using the concanavalin A (ConA) model of hepatitis, we investigated the regulation of inflammatory cytokine tumor necrosis factor (TNF)-α in the liver tissue and the blood after acupuncture stimulation at ST36. Methods: Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…On the other hand, vagotomy strongly suppresses acupuncture effects. 130 Sepsis, often leading to myocardial injury, is effectively abolished by EA at ST36, which reduces TNF-α and NO levels, thereby strongly inhibiting neutrophil accumulation, and lowering the plasma activity of CK-MB. Upon vagotomy, EA stimulation shows considerably fewer anti-inflammatory and protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, vagotomy strongly suppresses acupuncture effects. 130 Sepsis, often leading to myocardial injury, is effectively abolished by EA at ST36, which reduces TNF-α and NO levels, thereby strongly inhibiting neutrophil accumulation, and lowering the plasma activity of CK-MB. Upon vagotomy, EA stimulation shows considerably fewer anti-inflammatory and protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture at ST36, CV4, and KI1 was reported to reduce inflammatory factors, such as TNF- α , and inflammatory cell infiltration in a nonalcoholic fatty liver disease model [ 35 ]. Moreover, MA at ST36 regulated inflammatory factors in hepatitis models [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since activated p-ERK1/2 is known to induce TNF-α production in hepatic Kupffer cells, this study investigated CD68 and CD11b proteins as marker proteins of activated Kupffer cells. These results showed that the anti-inflammatory effect of acupuncture is mediated by vagus nerve activity modulating ERK1/2-STAT3 signaling cascade linked to the cholinergic anti-inflammatory mechanism ( 31 ).…”
Section: Resultsmentioning
confidence: 98%